Search for a narrow tt̄ resonance in pp̄ collisions at √s=1.96TeV - Abazov, V. M. (2012)
We report a search for a narrow tt̄ resonance that decays into a lepton+jets final state based on an integrated luminosity of 5.3fb -1 of proton-antiproton collisions at √s=1.96TeV collected by the D0 Collaboration at the Fermilab Tevatron Collider. We set upper limits on the production cross section of such a resonance multiplied by its branching fraction to tt̄. We exclude a leptophobic topcolor Z ′ at the 95% confidence level for masses below 835 GeV (940 GeV) if its width is 1.2% (3%) of its mass. We also exclude color octet vector bosons (colorons) with masses below 775 GeV. © 2012 American Physical Society.